INVOLVEMENT OF FOREIGN STUDENTS FROM TECHNICAL SPECIALTIES IN UKRANIAN SPEECH ACTIVITY OF PROFESSIONAL ORIENTATION (EDUCATION IN THE 21ST CENTURY, 2023)
Involvement of foreign students in Ukrainian speech activity of professional orientation was defined as one of pedagogical conditions for forming the Ukrainian professional and communicative competence of future foreign specialists from technical specialties within the research of Ukrainian training of future foreign specialists from technical specialties. The entity of basic concepts of the pedagogical condition as "activity", "activation", "activization" has been offered in the article. Scientific perspectives to a problem of activity in education have been investigated. The factors promoting Ukrainian speech activity of future specialists from technical specialties have been defined such as: 1) the organization of educational process, it promotes initiativity and independence of foreign students, strong and deep acquisition of knowledge, development of necessary skills, development of observation, thinking and speech, memory and creative imagination; 2) forming the student’s ability in order to adapt to conditions of the educational environment, to conform to it, to imitate the activity of other representatives of this environment; 3) the detailed psychological analysis of the identity of future specialist and comparison of his results with conditions of educational environment in order to forecast different types of activity; 4) adequate perception of people, assessment of other person and existence of interest in this assessment of the future specialist; 5) student’s enjoyment of educational activity and results of the efforts; 6) forming of the favorable attitude of a foreign student towards the discipline "Ukrainian as a foreign language" and to Ukrainian in general, etc.The analysis of the concept "activity" and selection of its important features for understanding the process of foreign students’ involvement in Ukrainian speech activity of professional orientation as a pedagogical condition for the Ukrainian professional and communicative competence formation of future foreign specialists from technical specialties allows to increase the level of planning of classwork and extra-curricular work, to develop professional and communicative tasks and motivational exercises, as well as to introduce the pedagogical methods providing improvement of internal (personal) qualities of the student and external conditions of professional and speech training.
Keywords: Ukrainian-speaking speech activity, activity, activation, activation